Perancangan Ui/Ux Website Safe Tangkinspec Dengan Design Thinking: Case Study Pertamina Integrated Terminal Kendari - Chairunnisa, Fadhillah; Faqihuddin Hanif, Isa (Arcitech: Journal of Computer Science and Artificial Intelligence, 2025)
This study aims to design a web-based User Interface (UI) and User Experience (UX) for the Safe Tangkinspec system as a digital solution for the inspection process of tanker vehicles at PT Pertamina Integrated Terminal Kendari. The previous inspection process, which relied on manual procedures using physical documents (hardcopy), was prone to human error, document loss, high operational costs, and delays in record-keeping. The Design Thinking methodology was applied through five stages: empathize, define, ideate, prototype, and test. This approach allowed for the identification of user needs and the development of a web-based solution with key features including digital forms, history tracking, schedule notifications, and a real-time dashboard. Usability testing using the System Usability Scale (SUS) yielded a score of 88%, categorized as “Excellent,” demonstrating that the interface is intuitive and effective for operational staff, and supports sustainable digital transformation in the energy sector. This research provides a practical contribution to the development of user-centered digital interfaces within the context of industrial infrastructure.